1997
DOI: 10.1103/physrevlett.78.3543
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Vortex Lattice Melting in YBa2Cu3et al.

Abstract: We report 89 Y and 17 O NMR (9 T) echo decays for YBa 2 Cu 3 O 7 and correct for contributions from dipolar coupling 63,65 Cu in order to isolate effects of vortex dynamics. We confirm vortex localization in the solid state with rms displacements consistent with Langevin dynamical theory, but with motional dynamics at time scales ͑10 100 ms͒ some ϳ10 6 times slower than predicted. Vortex migration over longer time scales is restricted to distances less than 1/100 of an intervortex spacing over times as long as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
5
25
0
Order By: Relevance
“…In the present case the reduction of the echo intensity is ascribed to the changes of average local hyperfine field resulting from changes of average orientation of the Mn moments which are maximum at off equilibrium and decrease to zero as the final thermal equilibrium is reached. A possible effect on the dephasing of the proton echo due to the interaction with the 57 Mn nuclei (similar to what is observed in superconductors [25]) cannot be easily explored for lack of information on the 57 Mn NMR.…”
Section: (Received 28 September 1999)mentioning
confidence: 90%
“…In the present case the reduction of the echo intensity is ascribed to the changes of average local hyperfine field resulting from changes of average orientation of the Mn moments which are maximum at off equilibrium and decrease to zero as the final thermal equilibrium is reached. A possible effect on the dephasing of the proton echo due to the interaction with the 57 Mn nuclei (similar to what is observed in superconductors [25]) cannot be easily explored for lack of information on the 57 Mn NMR.…”
Section: (Received 28 September 1999)mentioning
confidence: 90%
“…The separation of hyperfine relaxation from other mechanisms is more difficult to achieve in the copper oxides [14]. We find that below T ~ 25 K the spin lattice relaxation in κ-(ET) 2 Cu[N(CN) 2 ]Br develops a stretched exponential time dependence whose exponent β exhibits no apparent change at T C .…”
mentioning
confidence: 84%
“…It was also shown that T −1 2 in YBa 2 Cu 3 O 7−x has similar behavior at different crystallographic positions, 89 Y and both 17 O sites, suggesting that the relaxation has a common origin likely determined by vortex vibrations. [39,48] Although the theory [49] for vortex dynamics is not settled, as we shall discuss next, nonetheless its affect on T show a non-monotonic correspondence between relaxation and local magnetic field, Fig. 10, much more so than can be accounted for by any combination of Doppler shifts and broadened Redfield patterns for the distribution of local fields.…”
Section: Vortex Coresmentioning
confidence: 99%